An examination of the politico-literary strategies of some Third World writers - Williams, Keith Christopher (Department of English Language and Literature, 2016)
In this study I attempted to examine the politico-literary strategies of some "Third World" writers. I used the Marxian notions of class and ideology in order to investigate how writers' biographies determined their literary interpretations. Basic writings of Karl Marx, Frederick Engels and the theoretical work of Janet Wolff were used in this respect. I also used the Marxian concept of Historical Materialism in order to distinguish progressive interpretations from reactionary ones. The critical writing of Ernst Fischer was used in order to show that there was no unbridgeable gap between theoretical work in the "Third World" and the development of the aesthetic in Europe. The notion of socialist realism was of particular interest here. Notions of neo-colonialism and cultural imperialism were examined in order to set the context in which "Third World" authors write. The use of the mode of realism by these authors was investigated. The work of Hayden White was used to establish the fact that versions of history depend upon an author's moral purpose. The link was made between authors' moral purposes, their ideologies and their literary strategies. Literary analysis of some works by "Third World" authors was undertaken in order to see whether or not the authors succeeded in their attempts to give progressive interpretations of their historical contexts. Three "Third World" novels, that is, Ngugi wa Thiong'o's Petals of Blood, Sembene Ousmane's God's Bits of Wood and Gabriel Garcia Marquez's One Hundred Years of Solitude were examined in this regard. It was finally concluded that literary strategies have a material basis which is founded on the authors' life experiences and the historical context in which they write. This material bas is to the creative act is proposed as a way out of the labyrinth of textuality to which a "deconstructionalist" approach leads the critic.